Length changes of Austrian glaciers in 2017/2018 - Gerhard Karl Lieb; Andreas Kellerer-Pirklbauer (PANGAEA, 2021)
Glacier length change data of 96 Austrian glaciers were collected for the period summer/autumn 2017 to summer/autumn 2018 (variable periods depending on specific measurement dates). The measurements in 2018 have been carried out by 19 different teams led by one or two investigators per team. The 96 monitored glaciers are well distributed over the glaciated mountain ranges of the Austrian Alps and consider both small and some of the largest glaciers (up to ca.15 km^2) in Austria. Therefore, this sample is considered to be representative for all present-day glaciers in Austria. The monitored glaciers extend from latitude 46°33 extquotesingleN to 47°30 extquotesingleN and longitude 10°04 extquotesingleE to 13°39 extquotesingle E. The data published here comprise the glacier-length-change results for the glaciological year 2017-2018 and are based on a paper published in the official magazine of the Austrian Alpine Club named Bergauf (https://www.alpenverein.at/bk/bergauf/bergauf2019/Bergauf_2_2019/). The collected data are also stored in the database of the World Glacier Monitoring Service (WGMS) in Zurich, Switzerland (https://wgms.ch/). Glacier changes at the 96 glaciers was measured in different ways. First, at 69 Austrian glaciers the position of the glacier terminus was quantified for 2017 and 2018 by measuring the distance between distinct marked points in the proglacial area and the ice margin in clearly defined directions (azimuths) for both years. The difference of the measured distances in 2017 and 2018 yields the glacier length change for one specific point. By calculating the arithmetic mean of several of such marked points at a given glacier in 2017/2018, the glacier change value was obtained for glaciers with more than one marked point. Second, at seven Austrian glaciers the position of the glacier terminus was quantified for 2017 and 2018 using Global Navigation Satellite System (GNSS) techniques or other geodetic instruments measuring the glacier terminus for both years. Based on these two GNSS data sets, the glacier length change value was calculated for 2017/2018. Third, at eleven sites the glacier retreat was calculated for a period of two (2016/2018) or three (2015/2018) years using the first method described. Fourth, for six glaciers the change of the glacier position was qualitatively determined by photograph comparison. Results of our analysis show that 89 glaciers retreated, and 4 glaciers were stationary (i.e., no significant frontal change). For three glaciers it was not possible to quantify glacier change rates for 2017/2018 due to missing data or inaccessibility. The mean value of the glacier retreat rate of the 76 glaciers measured in 2017 and 2018 was 17.2 m/a. The highest glacier retreat value was 128.2 m/a measured at Viltragen Glacier, Venediger Mountains. Regarding the wider context, glacier length changes of Austrian Glaciers are measured annually within the framework of a monitoring program of the Austrian Alpine Club. This program is one of the longest glacier monitoring programs and runs since 1891. Measurements of length variations in Austria at single glaciers have been started even earlier dating back to 1878 at Pasterze Glacier. Since that year, glaciological surveys have been carried out almost annually at Pasterze Glacier representing one of the longest time series of continuous glacier monitoring worldwide. For more details regarding the glacier monitoring program of the Austrian Alpine Club visit https://www.alpenverein.at/portal/museum-archiv/gletschermessdienst/index.php (only in German).